2005
DOI: 10.1016/j.tcs.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Linear-time algorithms for the Hamiltonian problems on distance-hereditary graphs

Abstract: A Hamiltonian path of a graph G is a simple path that contains each vertex of G exactly once. A Hamiltonian cycle of a graph is a simple cycle with the same property. The Hamiltonian path (resp. cycle) problem involves testing whether a Hamiltonian path (resp. cycle) exists in a graph. The 1HP (resp. 2HP) problem is to determine whether a graph has a Hamiltonian path starting from a specified vertex (resp. starting from a specified vertex and ending at the other specified vertex). The Hamiltonian problems incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…It is sure that the Hamiltonian cycle problem is one of most well known NP-hard problem, and it is still NP-hard even for a chordal graph, and that an O( |V | + |E| ) time algorithm is known for distance hereditary graphs [17]. Here, we show that the Hamiltonian cycle problem can be solved in O( |V | ) time using the technique if a ptolemaic graph is given in the tree representation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is sure that the Hamiltonian cycle problem is one of most well known NP-hard problem, and it is still NP-hard even for a chordal graph, and that an O( |V | + |E| ) time algorithm is known for distance hereditary graphs [17]. Here, we show that the Hamiltonian cycle problem can be solved in O( |V | ) time using the technique if a ptolemaic graph is given in the tree representation.…”
Section: Introductionmentioning
confidence: 87%
“…Especially, Bandelt and Mulder showed that any distance hereditary graph can be obtained from K 2 by a sequence of extensions called "adding a pendant vertex" and "splitting a vertex." Using the characterizations, many efficient algorithms have been found for distance hereditary graphs [6,2,5,21,17,7]. However, the recognition of distance hereditary graphs in linear time is not so simple; Hammer and Maffray's algorithm [14] fails in some cases, and Damiand, Habib, and Paul's algorithm [9] requires to build a cotree in linear time (see [9,Chapter 4] for further details), where the cotree can be constructed in linear time by using recent algorithm based on multisweep LBFS approach by Bretscher, Corneil, Habib, and Paul [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hsieh et al [13] presented an O(n + m)-time sequential algorithm for the Hamiltonian problem on a distance-hereditary graph and also proposed a parallel implementation of their algorithm, which solves the problem in O(log n) time using O((n + m)/ log n) processors on a PRAM model. A unified approach to solving the Hamiltonian problems on distancehereditary graphs was presented in [14], while Hsieh [12] presented an efficient parallel strategy for the 2HP problem on the same class of graphs. Algorithms for the path cover problem on other classes of graphs were proposed in [2,15,22].…”
Section: Related Workmentioning
confidence: 99%
“…Although the original Hamiltonian path problem is proven to be an NPC problem [2], the time complexity of finding Hamiltonian cycles can be reduced to polynomial time under certain conditions, such as finding Hamiltonian cycles in distance-hereditary graphs [3], or in co-comparability graphs [4], or in semi-complete multipartite digraphs [5], and so on.…”
Section: Introduction Backgroundmentioning
confidence: 99%